Motivators and Barriers for Physical Activity among School-going Students in Chengalpattu District, Tamil Nadu, India: A Qualitative Study - Srinivasarengan Kamala Sampath; Padmasundari Singaram; Kalpana Kosalram (Journal of Clinical and Diagnostic Research, 2024)
Introduction: Participating in physical activity is crucial for the holistic development and well-being of children and adolescents. Research has shown that physical activity enhances metabolic, musculoskeletal, cardiovascular, psychosocial, and cognitive health. Among children and adolescents, it also improves cardiorespiratory and muscular fitness, and consistent engagement leads to reduced adiposity in overweight individuals. Aim: To explore the motivators and barriers to physical activity among adolescents. Materials and Methods: The study employs a qualitative phenomenological approach, utilising the Colaizzi method for data analysis. A total of 15 participants were selected via purposive sampling, and in-depth interviews were conducted from March to July 2023 in the Chengalpattu district of Tamil Nadu, India. Ethical considerations were observed, with participants providing informed consent. Results: The main themes were identified and categorised into motivators and barriers. Barriers include lack of time, access to fitness classes, interest or motivation, social support, psychological barriers and cost. Motivators encompass improved physical health, mental well-being, physical appearance, self-confidence, athletic and academic performance and a strong immune system. Conclusion: The study identified financial concerns, limited access to fitness classes, lack of interest or motivation, and inadequate social support as major barriers to physical activity. Motivators include a healthy immune system, improved physical health, mental well-being, self-confidence, and enhanced academic and athletic performance. To increase adolescent physical activity, it is essential to address academic demands and incorporate physical activity courses into the curriculum. Parental involvement in education and the use of effective motivational strategies are crucial.